Media, liberty and politics in Malaysia comparative studies on local dynamics and regional concerns - Mohd. Azizuddin Mohd. Sani (Penerbit Universiti Utara Malaysia, 2015)
[This book] is based on collection of 12 academic papers. This book traces the development and progress of Malaysia as a nation that embraces issues of media, liberty, and politics as essential parts of its culture, policy and well-being of the people.